Music and postwar transitions in the 19th and 20th centuries - Fléchet, Anaïs 1978-; Guerpin, Martin 1986-; Gumplowicz, Philippe 1950-; Kelly, Barbara ca. 20./21. Jh (Explorations in culture and international history, 2023)
Music and Postwar Transitions in the 19th and 20th Centuries is the first book to highlight the significance of the idea of 'postwar transition' in the field of music and to demonstrate how the contribution of musicians, composers, and their publics have influenced contemporary understandings of war. At the intersection of four domains including: the relationship between music and war culture, commemorative and consolatory dimensions of music, migration and exile, and the links between music, cultural diplomacy, and propaganda, leading historians, political scientists, psychologists, and musicologists explore disruptions and connections to music through the backdrop war. In turn, this volume sheds new light on what has been a blind spot in a growing historiography